2010
DOI: 10.1002/path.2734
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TGFβ–Smad signalling in experimental Pkd1 models and human patients with polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a common inherited renal disease characterized by many fluid-filled cysts and interstitial fibrosis in the kidneys, leading to chronic renal failure. During cystogenesis the renal tubules undergo extensive structural alterations that are accompanied by altered cellular signalling, directly and/or indirectly regulated by the PKD1 and PKD2 proteins. Since transforming growth factor (TGF)-beta signalling modulates cell proliferation, differentiation, apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 53 publications
2
80
1
1
Order By: Relevance
“…44 In mouse models in which Pkd1 can be conditionally inactivated, TGF-b signaling was not different from baseline in the early stages of cystogenesis; however, in later phases, cysts lining epithelial cells exhibited increased nuclear staining for pSmad2 along with increased expression of TGF-b target genes such as PAI-1. 45 Our cell culture data suggest that increased TGF-b ligands in the setting of ADPKD might result in an amplified response that could contribute to fibrosis and disease progression. Interestingly, a retrospective study of patients with MFS demonstrated an increased incidence of renal and hepatic cysts compared with an age/sex-matched control population.…”
Section: Discussionmentioning
confidence: 99%
“…44 In mouse models in which Pkd1 can be conditionally inactivated, TGF-b signaling was not different from baseline in the early stages of cystogenesis; however, in later phases, cysts lining epithelial cells exhibited increased nuclear staining for pSmad2 along with increased expression of TGF-b target genes such as PAI-1. 45 Our cell culture data suggest that increased TGF-b ligands in the setting of ADPKD might result in an amplified response that could contribute to fibrosis and disease progression. Interestingly, a retrospective study of patients with MFS demonstrated an increased incidence of renal and hepatic cysts compared with an age/sex-matched control population.…”
Section: Discussionmentioning
confidence: 99%
“…Pkd1 mutations lead to an earlier age of onset for ESRD than do Pkd2 mutations [18]. Cyst-lining epithelial cells exhibit increased nuclear staining for phosphorylated Smad2 and increased expression of TGF-β target genes such as collagen type I [19]. Microarray [20] studies of human ADPKD kidneys revealed that TGF-β and its downstream effectors are highly expressed in cystic epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] A plethora of cellular changes have been observed in cystic epithelium-like cells or tissues, including aberrant Ras/Raf/ERK activation, cAMP accumulation, as well as altered activation of Gproteins, mammalian target of rapamycin (mTOR), PI3-kinase, Jak2-STAT1/3, NFAT, TGFb, and NF-kb signaling. [6][7][8][9][10][11][12] Although there are currently no reliable therapies available and clinical management of ADPKD is mainly focused on managing complications, it is anticipated that new therapeutic interventions targeting these key molecular changes in PKD might prove effective. Clinical trials testing the efficacy of mTOR inhibitors were recently evaluated.…”
mentioning
confidence: 99%
“…11,25,26 These Pkd1 models were used to investigate the effects of low and high doses of sirolimus at different stages of the disease to determine whether a conventional low dose is as effective at reducing cyst formation and fibrosis as a higher dose, whether conventional low-dose sirolimus inhibits mTOR activity in cystic kidneys, and whether sirolimus is equally effective when initiated later in the disease course compared with early administration.…”
mentioning
confidence: 99%